/- Copyright (c) 2014 Jeremy Avigad. All rights reserved. Released under Apache 2.0 license as described in the file LICENSE. Authors: Jeremy Avigad, Leonardo de Moura -/ import algebra.group_power.order import algebra.big_operators.basic /-! # Definitions and properties of `gcd`, `lcm`, and `coprime` -/ namespace nat /-! ### `gcd` -/ theorem gcd_dvd (m n : ℕ) : (gcd m n ∣ m) ∧ (gcd m n ∣ n) := gcd.induction m n (λn, by rw gcd_zero_left; exact ⟨dvd_zero n, dvd_refl n⟩) (λm n npos, by rw ←gcd_rec; exact λ ⟨IH₁, IH₂⟩, ⟨IH₂, (dvd_mod_iff IH₂).1 IH₁⟩) theorem gcd_dvd_left (m n : ℕ) : gcd m n ∣ m := (gcd_dvd m n).left theorem gcd_dvd_right (m n : ℕ) : gcd m n ∣ n := (gcd_dvd m n).right theorem gcd_le_left {m} (n) (h : 0 < m) : gcd m n ≤ m := le_of_dvd h $ gcd_dvd_left m n theorem gcd_le_right (m) {n} (h : 0 < n) : gcd m n ≤ n := le_of_dvd h $ gcd_dvd_right m n theorem dvd_gcd {m n k : ℕ} : k ∣ m → k ∣ n → k ∣ gcd m n := gcd.induction m n (λn _ kn, by rw gcd_zero_left; exact kn) (λn m mpos IH H1 H2, by rw gcd_rec; exact IH ((dvd_mod_iff H1).2 H2) H1) theorem dvd_gcd_iff {m n k : ℕ} : k ∣ gcd m n ↔ k ∣ m ∧ k ∣ n := iff.intro (λ h, ⟨h.trans (gcd_dvd m n).left, h.trans (gcd_dvd m n).right⟩) (λ h, dvd_gcd h.left h.right) theorem gcd_comm (m n : ℕ) : gcd m n = gcd n m := dvd_antisymm (dvd_gcd (gcd_dvd_right m n) (gcd_dvd_left m n)) (dvd_gcd (gcd_dvd_right n m) (gcd_dvd_left n m)) theorem gcd_eq_left_iff_dvd {m n : ℕ} : m ∣ n ↔ gcd m n = m := ⟨λ h, by rw [gcd_rec, mod_eq_zero_of_dvd h, gcd_zero_left], λ h, h ▸ gcd_dvd_right m n⟩ theorem gcd_eq_right_iff_dvd {m n : ℕ} : m ∣ n ↔ gcd n m = m := by rw gcd_comm; apply gcd_eq_left_iff_dvd theorem gcd_assoc (m n k : ℕ) : gcd (gcd m n) k = gcd m (gcd n k) := dvd_antisymm (dvd_gcd ((gcd_dvd_left (gcd m n) k).trans (gcd_dvd_left m n)) (dvd_gcd ((gcd_dvd_left (gcd m n) k).trans (gcd_dvd_right m n)) (gcd_dvd_right (gcd m n) k))) (dvd_gcd (dvd_gcd (gcd_dvd_left m (gcd n k)) ((gcd_dvd_right m (gcd n k)).trans (gcd_dvd_left n k))) ((gcd_dvd_right m (gcd n k)).trans (gcd_dvd_right n k))) @[simp] theorem gcd_one_right (n : ℕ) : gcd n 1 = 1 := eq.trans (gcd_comm n 1) $ gcd_one_left n theorem gcd_mul_left (m n k : ℕ) : gcd (m * n) (m * k) = m * gcd n k := gcd.induction n k (λk, by repeat {rw mul_zero <|> rw gcd_zero_left}) (λk n H IH, by rwa [←mul_mod_mul_left, ←gcd_rec, ←gcd_rec] at IH) theorem gcd_mul_right (m n k : ℕ) : gcd (m * n) (k * n) = gcd m k * n := by rw [mul_comm m n, mul_comm k n, mul_comm (gcd m k) n, gcd_mul_left] theorem gcd_pos_of_pos_left {m : ℕ} (n : ℕ) (mpos : 0 < m) : 0 < gcd m n := pos_of_dvd_of_pos (gcd_dvd_left m n) mpos theorem gcd_pos_of_pos_right (m : ℕ) {n : ℕ} (npos : 0 < n) : 0 < gcd m n := pos_of_dvd_of_pos (gcd_dvd_right m n) npos theorem eq_zero_of_gcd_eq_zero_left {m n : ℕ} (H : gcd m n = 0) : m = 0 := or.elim (nat.eq_zero_or_pos m) id (assume H1 : 0 < m, absurd (eq.symm H) (ne_of_lt (gcd_pos_of_pos_left _ H1))) theorem eq_zero_of_gcd_eq_zero_right {m n : ℕ} (H : gcd m n = 0) : n = 0 := by rw gcd_comm at H; exact eq_zero_of_gcd_eq_zero_left H @[simp] theorem gcd_eq_zero_iff {i j : ℕ} : gcd i j = 0 ↔ i = 0 ∧ j = 0 := begin split, { intro h, exact ⟨eq_zero_of_gcd_eq_zero_left h, eq_zero_of_gcd_eq_zero_right h⟩, }, { rintro ⟨rfl, rfl⟩, exact nat.gcd_zero_right 0 } end theorem gcd_div {m n k : ℕ} (H1 : k ∣ m) (H2 : k ∣ n) : gcd (m / k) (n / k) = gcd m n / k := or.elim (nat.eq_zero_or_pos k) (λk0, by rw [k0, nat.div_zero, nat.div_zero, nat.div_zero, gcd_zero_right]) (λH3, nat.eq_of_mul_eq_mul_right H3 $ by rw [ nat.div_mul_cancel (dvd_gcd H1 H2), ←gcd_mul_right, nat.div_mul_cancel H1, nat.div_mul_cancel H2]) theorem gcd_greatest {a b d : ℕ} (hda : d ∣ a) (hdb : d ∣ b) (hd : ∀ e : ℕ, e ∣ a → e ∣ b → e ∣ d) : d = a.gcd b := (dvd_antisymm (hd _ (gcd_dvd_left a b) (gcd_dvd_right a b)) (dvd_gcd hda hdb)).symm theorem gcd_dvd_gcd_of_dvd_left {m k : ℕ} (n : ℕ) (H : m ∣ k) : gcd m n ∣ gcd k n := dvd_gcd ((gcd_dvd_left m n).trans H) (gcd_dvd_right m n) theorem gcd_dvd_gcd_of_dvd_right {m k : ℕ} (n : ℕ) (H : m ∣ k) : gcd n m ∣ gcd n k := dvd_gcd (gcd_dvd_left n m) ((gcd_dvd_right n m).trans H) theorem gcd_dvd_gcd_mul_left (m n k : ℕ) : gcd m n ∣ gcd (k * m) n := gcd_dvd_gcd_of_dvd_left _ (dvd_mul_left _ _) theorem gcd_dvd_gcd_mul_right (m n k : ℕ) : gcd m n ∣ gcd (m * k) n := gcd_dvd_gcd_of_dvd_left _ (dvd_mul_right _ _) theorem gcd_dvd_gcd_mul_left_right (m n k : ℕ) : gcd m n ∣ gcd m (k * n) := gcd_dvd_gcd_of_dvd_right _ (dvd_mul_left _ _) theorem gcd_dvd_gcd_mul_right_right (m n k : ℕ) : gcd m n ∣ gcd m (n * k) := gcd_dvd_gcd_of_dvd_right _ (dvd_mul_right _ _) theorem gcd_eq_left {m n : ℕ} (H : m ∣ n) : gcd m n = m := dvd_antisymm (gcd_dvd_left _ _) (dvd_gcd dvd_rfl H) theorem gcd_eq_right {m n : ℕ} (H : n ∣ m) : gcd m n = n := by rw [gcd_comm, gcd_eq_left H] -- Lemmas where one argument is a multiple of the other @[simp] lemma gcd_mul_left_left (m n : ℕ) : gcd (m * n) n = n := dvd_antisymm (gcd_dvd_right _ _) (dvd_gcd (dvd_mul_left _ _) dvd_rfl) @[simp] lemma gcd_mul_left_right (m n : ℕ) : gcd n (m * n) = n := by rw [gcd_comm, gcd_mul_left_left] @[simp] lemma gcd_mul_right_left (m n : ℕ) : gcd (n * m) n = n := by rw [mul_comm, gcd_mul_left_left] @[simp] lemma gcd_mul_right_right (m n : ℕ) : gcd n (n * m) = n := by rw [gcd_comm, gcd_mul_right_left] -- Lemmas for repeated application of `gcd` @[simp] lemma gcd_gcd_self_right_left (m n : ℕ) : gcd m (gcd m n) = gcd m n := dvd_antisymm (gcd_dvd_right _ _) (dvd_gcd (gcd_dvd_left _ _) dvd_rfl) @[simp] lemma gcd_gcd_self_right_right (m n : ℕ) : gcd m (gcd n m) = gcd n m := by rw [gcd_comm n m, gcd_gcd_self_right_left] @[simp] lemma gcd_gcd_self_left_right (m n : ℕ) : gcd (gcd n m) m = gcd n m := by rw [gcd_comm, gcd_gcd_self_right_right] @[simp] lemma gcd_gcd_self_left_left (m n : ℕ) : gcd (gcd m n) m = gcd m n := by rw [gcd_comm m n, gcd_gcd_self_left_right] -- Lemmas where one argument consists of addition of a multiple of the other @[simp] lemma gcd_add_mul_right_right (m n k : ℕ) : gcd m (n + k * m) = gcd m n := by simp [gcd_rec m (n + k * m), gcd_rec m n] @[simp] lemma gcd_add_mul_left_right (m n k : ℕ) : gcd m (n + m * k) = gcd m n := by simp [gcd_rec m (n + m * k), gcd_rec m n] @[simp] lemma gcd_mul_right_add_right (m n k : ℕ) : gcd m (k * m + n) = gcd m n := by simp [add_comm _ n] @[simp] lemma gcd_mul_left_add_right (m n k : ℕ) : gcd m (m * k + n) = gcd m n := by simp [add_comm _ n] @[simp] lemma gcd_add_mul_right_left (m n k : ℕ) : gcd (m + k * n) n = gcd m n := by rw [gcd_comm, gcd_add_mul_right_right, gcd_comm] @[simp] lemma gcd_add_mul_left_left (m n k : ℕ) : gcd (m + n * k) n = gcd m n := by rw [gcd_comm, gcd_add_mul_left_right, gcd_comm] @[simp] lemma gcd_mul_right_add_left (m n k : ℕ) : gcd (k * n + m) n = gcd m n := by rw [gcd_comm, gcd_mul_right_add_right, gcd_comm] @[simp] lemma gcd_mul_left_add_left (m n k : ℕ) : gcd (n * k + m) n = gcd m n := by rw [gcd_comm, gcd_mul_left_add_right, gcd_comm] -- Lemmas where one argument consists of an addition of the other @[simp] lemma gcd_add_self_right (m n : ℕ) : gcd m (n + m) = gcd m n := eq.trans (by rw one_mul) (gcd_add_mul_right_right m n 1) @[simp] lemma gcd_add_self_left (m n : ℕ) : gcd (m + n) n = gcd m n := by rw [gcd_comm, gcd_add_self_right, gcd_comm] @[simp] lemma gcd_self_add_left (m n : ℕ) : gcd (m + n) m = gcd n m := by rw [add_comm, gcd_add_self_left] @[simp] lemma gcd_self_add_right (m n : ℕ) : gcd m (m + n) = gcd m n := by rw [add_comm, gcd_add_self_right] /-! ### `lcm` -/ theorem lcm_comm (m n : ℕ) : lcm m n = lcm n m := by delta lcm; rw [mul_comm, gcd_comm] @[simp] theorem lcm_zero_left (m : ℕ) : lcm 0 m = 0 := by delta lcm; rw [zero_mul, nat.zero_div] @[simp] theorem lcm_zero_right (m : ℕ) : lcm m 0 = 0 := lcm_comm 0 m ▸ lcm_zero_left m @[simp] theorem lcm_one_left (m : ℕ) : lcm 1 m = m := by delta lcm; rw [one_mul, gcd_one_left, nat.div_one] @[simp] theorem lcm_one_right (m : ℕ) : lcm m 1 = m := lcm_comm 1 m ▸ lcm_one_left m @[simp] theorem lcm_self (m : ℕ) : lcm m m = m := or.elim (nat.eq_zero_or_pos m) (λh, by rw [h, lcm_zero_left]) (λh, by delta lcm; rw [gcd_self, nat.mul_div_cancel _ h]) theorem dvd_lcm_left (m n : ℕ) : m ∣ lcm m n := dvd.intro (n / gcd m n) (nat.mul_div_assoc _ $ gcd_dvd_right m n).symm theorem dvd_lcm_right (m n : ℕ) : n ∣ lcm m n := lcm_comm n m ▸ dvd_lcm_left n m theorem gcd_mul_lcm (m n : ℕ) : gcd m n * lcm m n = m * n := by delta lcm; rw [nat.mul_div_cancel' ((gcd_dvd_left m n).trans (dvd_mul_right m n))] theorem lcm_dvd {m n k : ℕ} (H1 : m ∣ k) (H2 : n ∣ k) : lcm m n ∣ k := or.elim (nat.eq_zero_or_pos k) (λh, by rw h; exact dvd_zero _) (λkpos, dvd_of_mul_dvd_mul_left (gcd_pos_of_pos_left n (pos_of_dvd_of_pos H1 kpos)) $ by rw [gcd_mul_lcm, ←gcd_mul_right, mul_comm n k]; exact dvd_gcd (mul_dvd_mul_left _ H2) (mul_dvd_mul_right H1 _)) theorem lcm_dvd_mul (m n : ℕ) : lcm m n ∣ m * n := lcm_dvd (dvd_mul_right _ _) (dvd_mul_left _ _) lemma lcm_dvd_iff {m n k : ℕ} : lcm m n ∣ k ↔ m ∣ k ∧ n ∣ k := ⟨λ h, ⟨(dvd_lcm_left _ _).trans h, (dvd_lcm_right _ _).trans h⟩, and_imp.2 lcm_dvd⟩ theorem lcm_assoc (m n k : ℕ) : lcm (lcm m n) k = lcm m (lcm n k) := dvd_antisymm (lcm_dvd (lcm_dvd (dvd_lcm_left m (lcm n k)) ((dvd_lcm_left n k).trans (dvd_lcm_right m (lcm n k)))) ((dvd_lcm_right n k).trans (dvd_lcm_right m (lcm n k)))) (lcm_dvd ((dvd_lcm_left m n).trans (dvd_lcm_left (lcm m n) k)) (lcm_dvd ((dvd_lcm_right m n).trans (dvd_lcm_left (lcm m n) k)) (dvd_lcm_right (lcm m n) k))) theorem lcm_ne_zero {m n : ℕ} (hm : m ≠ 0) (hn : n ≠ 0) : lcm m n ≠ 0 := by { intro h, simpa [h, hm, hn] using gcd_mul_lcm m n, } /-! ### `coprime` See also `nat.coprime_of_dvd` and `nat.coprime_of_dvd'` to prove `nat.coprime m n`. -/ instance (m n : ℕ) : decidable (coprime m n) := by unfold coprime; apply_instance theorem coprime_iff_gcd_eq_one {m n : ℕ} : coprime m n ↔ gcd m n = 1 := iff.rfl theorem coprime.gcd_eq_one {m n : ℕ} (h : coprime m n) : gcd m n = 1 := h theorem coprime.lcm_eq_mul {m n : ℕ} (h : coprime m n) : lcm m n = m * n := by rw [←one_mul (lcm m n), ←h.gcd_eq_one, gcd_mul_lcm] theorem coprime.symm {m n : ℕ} : coprime n m → coprime m n := (gcd_comm m n).trans theorem coprime_comm {m n : ℕ} : coprime n m ↔ coprime m n := ⟨coprime.symm, coprime.symm⟩ theorem coprime.symmetric : symmetric coprime := λ m n, coprime.symm theorem coprime.dvd_of_dvd_mul_right {m n k : ℕ} (H1 : coprime k n) (H2 : k ∣ m * n) : k ∣ m := let t := dvd_gcd (dvd_mul_left k m) H2 in by rwa [gcd_mul_left, H1.gcd_eq_one, mul_one] at t theorem coprime.dvd_of_dvd_mul_left {m n k : ℕ} (H1 : coprime k m) (H2 : k ∣ m * n) : k ∣ n := by rw mul_comm at H2; exact H1.dvd_of_dvd_mul_right H2 theorem coprime.dvd_mul_right {m n k : ℕ} (H : coprime k n) : k ∣ m * n ↔ k ∣ m := ⟨H.dvd_of_dvd_mul_right, λ h, dvd_mul_of_dvd_left h n⟩ theorem coprime.dvd_mul_left {m n k : ℕ} (H : coprime k m) : k ∣ m * n ↔ k ∣ n := ⟨H.dvd_of_dvd_mul_left, λ h, dvd_mul_of_dvd_right h m⟩ theorem coprime.gcd_mul_left_cancel {k : ℕ} (m : ℕ) {n : ℕ} (H : coprime k n) : gcd (k * m) n = gcd m n := have H1 : coprime (gcd (k * m) n) k, by rw [coprime, gcd_assoc, H.symm.gcd_eq_one, gcd_one_right], dvd_antisymm (dvd_gcd (H1.dvd_of_dvd_mul_left (gcd_dvd_left _ _)) (gcd_dvd_right _ _)) (gcd_dvd_gcd_mul_left _ _ _) theorem coprime.gcd_mul_right_cancel (m : ℕ) {k n : ℕ} (H : coprime k n) : gcd (m * k) n = gcd m n := by rw [mul_comm m k, H.gcd_mul_left_cancel m] theorem coprime.gcd_mul_left_cancel_right {k m : ℕ} (n : ℕ) (H : coprime k m) : gcd m (k * n) = gcd m n := by rw [gcd_comm m n, gcd_comm m (k * n), H.gcd_mul_left_cancel n] theorem coprime.gcd_mul_right_cancel_right {k m : ℕ} (n : ℕ) (H : coprime k m) : gcd m (n * k) = gcd m n := by rw [mul_comm n k, H.gcd_mul_left_cancel_right n] theorem coprime_div_gcd_div_gcd {m n : ℕ} (H : 0 < gcd m n) : coprime (m / gcd m n) (n / gcd m n) := by rw [coprime_iff_gcd_eq_one, gcd_div (gcd_dvd_left m n) (gcd_dvd_right m n), nat.div_self H] theorem not_coprime_of_dvd_of_dvd {m n d : ℕ} (dgt1 : 1 < d) (Hm : d ∣ m) (Hn : d ∣ n) : ¬ coprime m n := λ co, not_lt_of_ge (le_of_dvd zero_lt_one $ by rw [←co.gcd_eq_one]; exact dvd_gcd Hm Hn) dgt1 theorem exists_coprime {m n : ℕ} (H : 0 < gcd m n) : ∃ m' n', coprime m' n' ∧ m = m' * gcd m n ∧ n = n' * gcd m n := ⟨_, _, coprime_div_gcd_div_gcd H, (nat.div_mul_cancel (gcd_dvd_left m n)).symm, (nat.div_mul_cancel (gcd_dvd_right m n)).symm⟩ theorem exists_coprime' {m n : ℕ} (H : 0 < gcd m n) : ∃ g m' n', 0 < g ∧ coprime m' n' ∧ m = m' * g ∧ n = n' * g := let ⟨m', n', h⟩ := exists_coprime H in ⟨_, m', n', H, h⟩ @[simp] theorem coprime_add_self_right {m n : ℕ} : coprime m (n + m) ↔ coprime m n := by rw [coprime, coprime, gcd_add_self_right] @[simp] theorem coprime_self_add_right {m n : ℕ} : coprime m (m + n) ↔ coprime m n := by rw [add_comm, coprime_add_self_right] @[simp] theorem coprime_add_self_left {m n : ℕ} : coprime (m + n) n ↔ coprime m n := by rw [coprime, coprime, gcd_add_self_left] @[simp] theorem coprime_self_add_left {m n : ℕ} : coprime (m + n) m ↔ coprime n m := by rw [coprime, coprime, gcd_self_add_left] @[simp] lemma coprime_add_mul_right_right (m n k : ℕ) : coprime m (n + k * m) ↔ coprime m n := by rw [coprime, coprime, gcd_add_mul_right_right] @[simp] lemma coprime_add_mul_left_right (m n k : ℕ) : coprime m (n + m * k) ↔ coprime m n := by rw [coprime, coprime, gcd_add_mul_left_right] @[simp] lemma coprime_mul_right_add_right (m n k : ℕ) : coprime m (k * m + n) ↔ coprime m n := by rw [coprime, coprime, gcd_mul_right_add_right] @[simp] lemma coprime_mul_left_add_right (m n k : ℕ) : coprime m (m * k + n) ↔ coprime m n := by rw [coprime, coprime, gcd_mul_left_add_right] @[simp] lemma coprime_add_mul_right_left (m n k : ℕ) : coprime (m + k * n) n ↔ coprime m n := by rw [coprime, coprime, gcd_add_mul_right_left] @[simp] lemma coprime_add_mul_left_left (m n k : ℕ) : coprime (m + n * k) n ↔ coprime m n := by rw [coprime, coprime, gcd_add_mul_left_left] @[simp] lemma coprime_mul_right_add_left (m n k : ℕ) : coprime (k * n + m) n ↔ coprime m n := by rw [coprime, coprime, gcd_mul_right_add_left] @[simp] lemma coprime_mul_left_add_left (m n k : ℕ) : coprime (n * k + m) n ↔ coprime m n := by rw [coprime, coprime, gcd_mul_left_add_left] theorem coprime.mul {m n k : ℕ} (H1 : coprime m k) (H2 : coprime n k) : coprime (m * n) k := (H1.gcd_mul_left_cancel n).trans H2 theorem coprime.mul_right {k m n : ℕ} (H1 : coprime k m) (H2 : coprime k n) : coprime k (m * n) := (H1.symm.mul H2.symm).symm theorem coprime.coprime_dvd_left {m k n : ℕ} (H1 : m ∣ k) (H2 : coprime k n) : coprime m n := eq_one_of_dvd_one (by delta coprime at H2; rw ← H2; exact gcd_dvd_gcd_of_dvd_left _ H1) theorem coprime.coprime_dvd_right {m k n : ℕ} (H1 : n ∣ m) (H2 : coprime k m) : coprime k n := (H2.symm.coprime_dvd_left H1).symm theorem coprime.coprime_mul_left {k m n : ℕ} (H : coprime (k * m) n) : coprime m n := H.coprime_dvd_left (dvd_mul_left _ _) theorem coprime.coprime_mul_right {k m n : ℕ} (H : coprime (m * k) n) : coprime m n := H.coprime_dvd_left (dvd_mul_right _ _) theorem coprime.coprime_mul_left_right {k m n : ℕ} (H : coprime m (k * n)) : coprime m n := H.coprime_dvd_right (dvd_mul_left _ _) theorem coprime.coprime_mul_right_right {k m n : ℕ} (H : coprime m (n * k)) : coprime m n := H.coprime_dvd_right (dvd_mul_right _ _) theorem coprime.coprime_div_left {m n a : ℕ} (cmn : coprime m n) (dvd : a ∣ m) : coprime (m / a) n := begin by_cases a_split : (a = 0), { subst a_split, rw zero_dvd_iff at dvd, simpa [dvd] using cmn, }, { rcases dvd with ⟨k, rfl⟩, rw nat.mul_div_cancel_left _ (nat.pos_of_ne_zero a_split), exact coprime.coprime_mul_left cmn, }, end theorem coprime.coprime_div_right {m n a : ℕ} (cmn : coprime m n) (dvd : a ∣ n) : coprime m (n / a) := (coprime.coprime_div_left cmn.symm dvd).symm lemma coprime_mul_iff_left {k m n : ℕ} : coprime (m * n) k ↔ coprime m k ∧ coprime n k := ⟨λ h, ⟨coprime.coprime_mul_right h, coprime.coprime_mul_left h⟩, λ ⟨h, _⟩, by rwa [coprime_iff_gcd_eq_one, coprime.gcd_mul_left_cancel n h]⟩ lemma coprime_mul_iff_right {k m n : ℕ} : coprime k (m * n) ↔ coprime k m ∧ coprime k n := by simpa only [coprime_comm] using coprime_mul_iff_left lemma coprime.gcd_left (k : ℕ) {m n : ℕ} (hmn : coprime m n) : coprime (gcd k m) n := hmn.coprime_dvd_left $ gcd_dvd_right k m lemma coprime.gcd_right (k : ℕ) {m n : ℕ} (hmn : coprime m n) : coprime m (gcd k n) := hmn.coprime_dvd_right $ gcd_dvd_right k n lemma coprime.gcd_both (k l : ℕ) {m n : ℕ} (hmn : coprime m n) : coprime (gcd k m) (gcd l n) := (hmn.gcd_left k).gcd_right l lemma coprime.mul_dvd_of_dvd_of_dvd {a n m : ℕ} (hmn : coprime m n) (hm : m ∣ a) (hn : n ∣ a) : m * n ∣ a := let ⟨k, hk⟩ := hm in hk.symm ▸ mul_dvd_mul_left _ (hmn.symm.dvd_of_dvd_mul_left (hk ▸ hn)) theorem coprime_one_left : ∀ n, coprime 1 n := gcd_one_left theorem coprime_one_right : ∀ n, coprime n 1 := gcd_one_right theorem coprime.pow_left {m k : ℕ} (n : ℕ) (H1 : coprime m k) : coprime (m ^ n) k := nat.rec_on n (coprime_one_left _) (λn IH, H1.mul IH) theorem coprime.pow_right {m k : ℕ} (n : ℕ) (H1 : coprime k m) : coprime k (m ^ n) := (H1.symm.pow_left n).symm theorem coprime.pow {k l : ℕ} (m n : ℕ) (H1 : coprime k l) : coprime (k ^ m) (l ^ n) := (H1.pow_left _).pow_right _ @[simp] lemma coprime_pow_left_iff {n : ℕ} (hn : 0 < n) (a b : ℕ) : nat.coprime (a ^ n) b ↔ nat.coprime a b := begin obtain ⟨n, rfl⟩ := exists_eq_succ_of_ne_zero hn.ne', rw [pow_succ, nat.coprime_mul_iff_left], exact ⟨and.left, λ hab, ⟨hab, hab.pow_left _⟩⟩ end @[simp] lemma coprime_pow_right_iff {n : ℕ} (hn : 0 < n) (a b : ℕ) : nat.coprime a (b ^ n) ↔ nat.coprime a b := by rw [nat.coprime_comm, coprime_pow_left_iff hn, nat.coprime_comm] theorem coprime.eq_one_of_dvd {k m : ℕ} (H : coprime k m) (d : k ∣ m) : k = 1 := by rw [← H.gcd_eq_one, gcd_eq_left d] @[simp] theorem coprime_zero_left (n : ℕ) : coprime 0 n ↔ n = 1 := by simp [coprime] @[simp] theorem coprime_zero_right (n : ℕ) : coprime n 0 ↔ n = 1 := by simp [coprime] theorem not_coprime_zero_zero : ¬ coprime 0 0 := by simp @[simp] theorem coprime_one_left_iff (n : ℕ) : coprime 1 n ↔ true := by simp [coprime] @[simp] theorem coprime_one_right_iff (n : ℕ) : coprime n 1 ↔ true := by simp [coprime] @[simp] theorem coprime_self (n : ℕ) : coprime n n ↔ n = 1 := by simp [coprime] lemma gcd_mul_of_coprime_of_dvd {a b c : ℕ} (hac : coprime a c) (b_dvd_c : b ∣ c) : gcd (a * b) c = b := begin rcases exists_eq_mul_left_of_dvd b_dvd_c with ⟨d, rfl⟩, rw [gcd_mul_right], convert one_mul b, exact coprime.coprime_mul_right_right hac, end section big_operators open_locale big_operators /-- See `is_coprime.prod_left` for the corresponding lemma about `is_coprime` -/ lemma coprime_prod_left {ι : Type*} {x : ℕ} {s : ι → ℕ} {t : finset ι} : (∀ (i : ι), i ∈ t → coprime (s i) x) → coprime (∏ (i : ι) in t, s i) x := finset.prod_induction s (λ y, y.coprime x) (λ a b, coprime.mul) (by simp) /-- See `is_coprime.prod_right` for the corresponding lemma about `is_coprime` -/ lemma coprime_prod_right {ι : Type*} {x : ℕ} {s : ι → ℕ} {t : finset ι} : (∀ (i : ι), i ∈ t → coprime x (s i)) → coprime x (∏ (i : ι) in t, s i) := finset.prod_induction s (λ y, x.coprime y) (λ a b, coprime.mul_right) (by simp) end big_operators lemma coprime.eq_of_mul_eq_zero {m n : ℕ} (h : m.coprime n) (hmn : m * n = 0) : m = 0 ∧ n = 1 ∨ m = 1 ∧ n = 0 := (nat.eq_zero_of_mul_eq_zero hmn).imp (λ hm, ⟨hm, n.coprime_zero_left.mp $ hm ▸ h⟩) (λ hn, ⟨m.coprime_zero_left.mp $ hn ▸ h.symm, hn⟩) /-- Represent a divisor of `m * n` as a product of a divisor of `m` and a divisor of `n`. -/ def prod_dvd_and_dvd_of_dvd_prod {m n k : ℕ} (H : k ∣ m * n) : { d : {m' // m' ∣ m} × {n' // n' ∣ n} // k = d.1 * d.2 } := begin cases h0 : (gcd k m), case nat.zero { obtain rfl : k = 0 := eq_zero_of_gcd_eq_zero_left h0, obtain rfl : m = 0 := eq_zero_of_gcd_eq_zero_right h0, exact ⟨⟨⟨0, dvd_refl 0⟩, ⟨n, dvd_refl n⟩⟩, (zero_mul n).symm⟩ }, case nat.succ : tmp { have hpos : 0 < gcd k m := h0.symm ▸ nat.zero_lt_succ _; clear h0 tmp, have hd : gcd k m * (k / gcd k m) = k := (nat.mul_div_cancel' (gcd_dvd_left k m)), refine ⟨⟨⟨gcd k m, gcd_dvd_right k m⟩, ⟨k / gcd k m, _⟩⟩, hd.symm⟩, apply dvd_of_mul_dvd_mul_left hpos, rw [hd, ← gcd_mul_right], exact dvd_gcd (dvd_mul_right _ _) H } end theorem gcd_mul_dvd_mul_gcd (k m n : ℕ) : gcd k (m * n) ∣ gcd k m * gcd k n := begin rcases (prod_dvd_and_dvd_of_dvd_prod $ gcd_dvd_right k (m * n)) with ⟨⟨⟨m', hm'⟩, ⟨n', hn'⟩⟩, h⟩, replace h : gcd k (m * n) = m' * n' := h, rw h, have hm'n' : m' * n' ∣ k := h ▸ gcd_dvd_left _ _, apply mul_dvd_mul, { have hm'k : m' ∣ k := (dvd_mul_right m' n').trans hm'n', exact dvd_gcd hm'k hm' }, { have hn'k : n' ∣ k := (dvd_mul_left n' m').trans hm'n', exact dvd_gcd hn'k hn' } end theorem coprime.gcd_mul (k : ℕ) {m n : ℕ} (h : coprime m n) : gcd k (m * n) = gcd k m * gcd k n := dvd_antisymm (gcd_mul_dvd_mul_gcd k m n) ((h.gcd_both k k).mul_dvd_of_dvd_of_dvd (gcd_dvd_gcd_mul_right_right _ _ _) (gcd_dvd_gcd_mul_left_right _ _ _)) theorem pow_dvd_pow_iff {a b n : ℕ} (n0 : 0 < n) : a ^ n ∣ b ^ n ↔ a ∣ b := begin refine ⟨λ h, _, λ h, pow_dvd_pow_of_dvd h _⟩, cases nat.eq_zero_or_pos (gcd a b) with g0 g0, { simp [eq_zero_of_gcd_eq_zero_right g0] }, rcases exists_coprime' g0 with ⟨g, a', b', g0', co, rfl, rfl⟩, rw [mul_pow, mul_pow] at h, replace h := dvd_of_mul_dvd_mul_right (pow_pos g0' _) h, have := pow_dvd_pow a' n0, rw [pow_one, (co.pow n n).eq_one_of_dvd h] at this, simp [eq_one_of_dvd_one this] end lemma gcd_mul_gcd_of_coprime_of_mul_eq_mul {a b c d : ℕ} (cop : c.coprime d) (h : a * b = c * d) : a.gcd c * b.gcd c = c := begin apply dvd_antisymm, { apply nat.coprime.dvd_of_dvd_mul_right (nat.coprime.mul (cop.gcd_left _) (cop.gcd_left _)), rw ← h, apply mul_dvd_mul (gcd_dvd _ _).1 (gcd_dvd _ _).1 }, { rw [gcd_comm a _, gcd_comm b _], transitivity c.gcd (a * b), rw [h, gcd_mul_right_right d c], apply gcd_mul_dvd_mul_gcd } end /-- If `k:ℕ` divides coprime `a` and `b` then `k = 1` -/ lemma eq_one_of_dvd_coprimes {a b k : ℕ} (h_ab_coprime : coprime a b) (hka : k ∣ a) (hkb : k ∣ b) : k = 1 := begin rw coprime_iff_gcd_eq_one at h_ab_coprime, have h1 := dvd_gcd hka hkb, rw h_ab_coprime at h1, exact nat.dvd_one.mp h1, end lemma coprime.mul_add_mul_ne_mul {m n a b : ℕ} (cop : coprime m n) (ha : a ≠ 0) (hb : b ≠ 0) : a * m + b * n ≠ m * n := begin intro h, obtain ⟨x, rfl⟩ : n ∣ a := cop.symm.dvd_of_dvd_mul_right ((nat.dvd_add_iff_left (dvd_mul_left n b)).mpr ((congr_arg _ h).mpr (dvd_mul_left n m))), obtain ⟨y, rfl⟩ : m ∣ b := cop.dvd_of_dvd_mul_right ((nat.dvd_add_iff_right (dvd_mul_left m (n*x))).mpr ((congr_arg _ h).mpr (dvd_mul_right m n))), rw [mul_comm, mul_ne_zero_iff, ←one_le_iff_ne_zero] at ha hb, refine mul_ne_zero hb.2 ha.2 (eq_zero_of_mul_eq_self_left (ne_of_gt (add_le_add ha.1 hb.1)) _), rw [← mul_assoc, ← h, add_mul, add_mul, mul_comm _ n, ←mul_assoc, mul_comm y] end end nat